The role of inflammation and macrophage accumulation in the development of obesity induced Type 2 diabetes mellitus and the possible therapeutic effects of long chain n-3 polyunsaturated fatty acids - Oliver, Elizabeth (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2010)
Obesity gives rise to a state of chronic, low-grade inflammation characterised by inflamed white adipose tissue (WAT) with increased infiltration of macrophages termed adipose tissue macrophages (ATM). These ATM produce pro-inflammatory cytokines, which are proposed to alter the endocrine function of the WAT and disrupt insulin signalling. High intakes of long chain (LC) n-3 polyunsaturated fatty acids (PUFA) such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) are known to modulate immune cell function and may exert therapeutic effects on obesity induced insulin resistance and type 2 diabetes mellitus (T2DM). The objective of this thesis was to investigate the molecular mechanisms, which mediate the interaction between macrophages and adipocytes. An in vivo IL-1 type 1 receptor knock out (IL-1RI-/-) mouse model followed by a series of in vitro experiments, including a co-culture of adipocytes and macrophages were examined. The effects of LC n-3 PUFA treatment were assessed in adipocytes and macrophages both independently and in the co-culture system.
Keywords: Neutrigenomics, Ph.D.; Ph.D. Trinity College Dublin